Globalization from Below: The Power of Solidarity - Wells, Don (Relations industrielles / Industrial Relations, 2002)
Globalization from Below: The Power of Solidarity by Jeremy Brecher, Tim Costello, and Brendan Smith, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Globalization; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social activism; Working conditions